White women writing the (post)colony : creolite, home and estrangement in novels by Rhys, Duras and Van Niekerk - Van Houwelingen, Caren (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.